Features of iPad language applications for speech-language therapy with children - Heyman, Nikki (My University, 2017)
Background: Speech-Language Pathologists (SLPs) worldwide are using apps in their interventions. Despite this growing trend, there is limited literature on the use of apps for language intervention. Reports indicate that SLPs are selecting apps by word-of-mouth and popularity. One of the difficulties in evaluating apps is related to the lack of consensus about which features are important in an app when providing speech-language therapy to children. Aim: This study aimed to investigate the features of apps that SLPs regard as valuable for language intervention with children and how SLPs were using apps in their intervention. Method: The study employed an explanatory, sequential mixed-method approach using SLPs in 6 predominantly English-speaking countries. A self-developed online survey (N = 338) identifying the features of apps was distributed to SLPs who use apps. This was followed by a semi-structured interview with some participants (n = 16) in order to obtain further insights from the survey. Descriptive statistics were used to examine the survey results. Interview data were explored using thematic analysis. Findings: The findings show that SLPs view apps as an engaging and motivating tool for therapy to facilitate their intervention goals. The lack of guidelines to support SLPs in their selection of apps has contributed to the selection of apps based on popularity and word-of-mouth rather than feature matching. Findings showed that specific content and design features of apps may support effective intervention, however these features need to be carefully evaluated in terms of the underlying principles of language intervention, multimedia learning and learning. Features that may impede effective intervention must also be considered. In addition, the social and pragmatic aspects of communication must be contemplated when using apps. Conclusions: A feature-matching checklist was developed in order to assist SLPs select apps based on feature matching. The findings from the study highlight the need for SLPs to engage more deeply with the theory underlying multimedia learning so that this information can be used to contribute to evidence-based practice when using apps for intervention. This study, calls for SLPs to make a concerted effort to engage in research around apps and app use.
A dissertation submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree Master in Speech-Language Pathology
Keywords: Speech therapy for children--Data processing; Speech therapists; iPad (Computer); Application software